Forme e contenuti del pensiero delirante - Petrucci, Manuela; Giorgini, Luca (Il sogno della farfalla, 2020)
In this article the authors present some of the theoretical research findings and hypotheses about delusion by the famous Italian psychiatrist Silvano Arieti, based on his book Interpretation of Schizophrenia (1955). In the first part of the paper, the origin of the modern definition of delusion is explained, as well as its connection with Karl Jaspers’ influence through his book General Pathology (1913). In the second part, Arieti’s interpretation of psychosis is schematically described, highlighting in particular his intent to cure schizophrenia. In order to clearly explain some arduous concepts, such as teleological thinking and Von Domarus Principle, a selection of movie scenes are pinpointed. In the conclusion, the authors discuss the theoretical limitations of Arieti and suggest a more modern possibility for psychotherapeutic treatment of psychosis.